2016
DOI: 10.1007/s00213-016-4262-5
|View full text |Cite
|
Sign up to set email alerts
|

Severity of dependence modulates smokers’ functional connectivity in the reward circuit: a preliminary study

Abstract: Our results indicate a dysfunction of the reward circuit in nicotine-dependent individuals. Moreover, our study improves the understanding of the neuroplastic changes that occur during the development of nicotine dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 68 publications
2
16
0
Order By: Relevance
“…The result may suggest the key role of tobacco dependence in smokers’ insula‐based rsFC. In the reward circuit, a positive correlation between the inter‐hippocampus rsFC and FTND was detected among all smokers in resting state . Both the reward circuit and insula play important roles in tobacco dependence.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The result may suggest the key role of tobacco dependence in smokers’ insula‐based rsFC. In the reward circuit, a positive correlation between the inter‐hippocampus rsFC and FTND was detected among all smokers in resting state . Both the reward circuit and insula play important roles in tobacco dependence.…”
Section: Discussionmentioning
confidence: 91%
“…Previous research has explored the changes of rsFC caused by smoking in ventral and dorsal striatum, frontostriatal region, prefrontal and limbic regions, insula and parahippocampus . Widespread rsFC attenuation was observed in the reward circuit of smokers compared with non‐smokers . In young smokers, reduced rsFC was found between caudate and dorsolateral prefrontal cortex and orbitofrontal cortex …”
Section: Introductionmentioning
confidence: 99%
“…However, individuals with shorter smoking history showed weaker fALFF in the left precuneus and right ITG/IOG, whereas those with longer smoking history showed stronger fALFF which was closer to the fALFF value of the nonsmokers. Similar resting-state functional connectivity (rsFC) study showed widespread rsFC attenuation in the reward circuit in smokers and the rsFC was positively correlated with dependence severity 33 . Moreover, microstructural studies found that the generally higher fractional anisotropy (FA) seen in smokers may reflect an increase in FA that follows the initiation of smoking, but prolonged smoking appears to reverse this effect with a progressive decline in FA with increasing pack-years of smoking 34, 35 .…”
Section: Discussionmentioning
confidence: 78%
“…Several functional brain imaging studies reported that occipital areas were activated following smoking or nicotine exposure during visual task performance 31, 32 . Activated occipital areas have been regarded as neural correlates of nicotine-induced attention increase 32, 33 .…”
Section: Discussionmentioning
confidence: 99%
“…NIC modifies the release of NT and their functions. [10,[13][14] NT is a chemical released from a nerve ending. The transmission of a neuron depends on the action of specific NT on specific receptors.…”
mentioning
confidence: 99%